Political Theory and Praxis : New Perspectives. - Ball, Terence (University of Minnesota Press, 1977)
Part I: Origins. On the History of "Theory" and "Praxis" by Nicholas Lobkowicz. Creatures of a Day: Thought and Action in Thucydides by J. Peter Euben. Plato and Aristotle: The Unity Versus the Autonomy of Theory and Practice by Terence Ball. Part II: Dev.